The upregulated LsKN1 gene transforms pinnately to palmately lobed leaves through auxin, gibberellin, and leaf dorsiventrality pathways in lettuce. Issue 9 (2nd July 2022) - Wang, Menglu; Lavelle, Dean; Yu, Changchun; Zhang, Weiyi; Chen, Jiongjiong; Wang, Xin; Michelmore, Richard W; Kuang, Hanhui
Summary: Leaf shape represents a vital agronomic trait for leafy vegetables such as lettuce. Some lettuce cultivars produce lobed leaves, varying from pinnately to palmately lobed, but the genetic mechanisms remain unclear. In this study, we cloned one major quantitative trait locus (QTL) controlling palmately lobed leaves. The candidate gene, LsKN1, encodes a homeobox transcription factor, and has been shown previously to be critical for the development of leafy heads in lettuce. The LsKN1 allele that is upregulated by the insertion of a transposon promotes the development of palmately lobed leaves. We demonstrated that LsKN1 upregulated LsCUC2 and LsCUC3 through different mechanisms, and their upregulation was critical for the development of palmately lobed leaves. LsKN1 binds the promoter of LsPID to promote auxin biosynthesis, which positively contributes to the development of palmately lobed leaves. In contrast, LsKN1 suppresses GA biosynthesis to promote palmately lobed leaves. LsKN1 also binds to the promoter of LsAS1, a dorsiventrality gene, to downregulate its expression. Overexpression of the LsAS1 gene compromised the effects of the LsKN1 gene changing palmately to pinnately lobed leaves. Our study illustrated that the upregulated LsKN1 gene led to palmately lobed leaves in lettuce by integrating several downstream pathways, including auxin, gibberellin, and leaf dorsiventrality pathways. Abstract : Cultivated lettuce ( Lactuca sativa ), domesticated from prickly lettuce ( L. serriola ), is one of the most important green leafy vegetables worldwide. Lettuce is also a model species for hydroponics, and an ideal plant to be engineered to produce oral vaccines or valuable pharmaceuticals. Leaf shape is an important trait for plant species, and leaf shape per se is an agronomic trait for leafy vegetables such as lettuce. Lobed leaves have been studied in several species. However, the mechanism underlying the variation between pinnately and palmately lobed leaves remain unclear. For the first time, we dissected the genetic mechanisms underlying palmately lobed leaves in plants, providing novel insights on leaf development. The palmately lobed leaves contribute to the sensory quality of lettuce, and our results will facilitate the breeding of lettuce cultivars with ideal leaf shapes.